Kinesik Berkonteks Maluku dalam Film Cahaya Dari Timur Beta Maluku (Kajian Pragmatik) - Wally, Firman; Maisaroh, Siti; Martutik, (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research examines kinesics, or the study of body movements in nonverbal communication. It aims to describe the forms and meanings of kinesics in the cultural context of Maluku, as depicted in the film Cahaya dari Timur Beta Maluku, from a pragmatic perspective. This research employs a qualitative descriptive method. The data source is the film Cahaya dari Timur Beta Maluku, with the research data consisting of nonverbal kinesic language. Data collection was conducted using observation and documentation techniques. The data analysis process involved: (1) selecting and verifying the clarity and completeness of the collected data, (2) identifying data that referred to kinesic nonverbal language, (3) categorizing the data, (4) describing the data, and (5) drawing conclusions from the research findings. The results of the study reveal three types of kinesics found in the film: facial expressions, body movements, and body positions. The facial expressions include raised eyebrows. Body movements in the film encompass hand gestures, head movements, and body motions resembling the traditional Cakalele dance. Body positions include movements of approaching and distancing. This study demonstrates that kinesics in the film serves not only as a technical visual aspect but also as a medium of nonverbal communication that enriches viewers’ interpretation of the characters and the cultural atmosphere of Maluku.